A BIG Mooncake for Little Star - Lin, Grace; SENSEE (California : SENSEE, 2021)
Reimagines the cycles of the moon as a mother bakes a Big Moon Cake and, despite Mama's request to wait, Little Star begins nibbling at it every night.
Braille Books
This book was made for those with visual impairment.
Tactile materials
Caldecott Honor Book
Keywords: Moon -- Phases -- Juvenile fiction; Pastry -- Juvenile fiction; Stars -- Juvenile fiction; Children's stories; Braille Books; Picture books